The Modifying Effect of PD6G Enzyme on Favism Disease - Saad-allah, Nabaa Qassim (American Journal of Biomedicine and Pharmacy, 2025)
Favism (the acute hemolytic episode that occurs after eating fava beans) can be a major health problem in individuals with glucose–6–phosphate dehydrogenase (G6PD) deficiency. In the 1980s, phenotyping studies showed that the variant G6PD Mediterranean was associated with severe symptoms of favism in affected males. The possession of high levels of the enzyme phosphogluconate dehydrogenase (PD6G), already described at that time, was unexpectedly found to correlate with the mildest form of that disorder, the G6PD A– variant. Available data indicate that PD6G plays a role in favouring the maintenance of a better redox balance, thus protecting red blood cells from oxidative stress . In G6PD–deficient subjects, the absence or deficiency of the G6PD enzyme leads to decreased synthesis of NADPH, thereby impairing the activity of the glutathione reductase and glutathione peroxidase systems and precipitating an oxidative–stress attack. It is acknowledged that deficiencies of either glucose–6–phosphate dehydrogenase or phosphogluconate dehydrogenase are related in the pentose–phosphate pathway, and that high levels of PD6G safely escort hexose–6–phosphates into the pathway. Therefore, PD6G can modulate the severity of favism by providing an alternative route for the oxidation of glucose–6–phosphate and glucose–1–phosphate.